2005
DOI: 10.1348/135532505x40836
|View full text |Cite
|
Sign up to set email alerts
|

Victimization of mentally ill patients living in the community: Is it a life‐style issue?

Abstract: Purpose. Although criminal victimization of mentally ill patients has been researched, what little work there is focuses on in‐patient samples. This study aimed to compare crimes against mentally ill patients living in the community with crimes against students who have a high life‐style risk of victimization. Methods. The samples were selected via community‐based mental health services and a university population. A group of 40 mentally ill patients and 80 students reported experiences of victimization in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Three out of the seven studies that adopted a survey approach used standardised measures (13, 8, 5). Both Wood & Edwards ( 2005 ) and Pettit et al . ( 2013 ) used an adapted version of the Crime Survey for England and Wales.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Three out of the seven studies that adopted a survey approach used standardised measures (13, 8, 5). Both Wood & Edwards ( 2005 ) and Pettit et al . ( 2013 ) used an adapted version of the Crime Survey for England and Wales.…”
Section: Resultsmentioning
confidence: 96%
“…According to Woods & Edwards ( 2005 ), those with mental health problems are more likely to experience victimisation by people they know as opposed to a student population who are more likely to be victimised by strangers. In some cases, neighbours or other tenants within their supported accommodation would ‘be-friend’ those with mental health problems in order to exploit them, for example, by borrowing money or cigarettes and never paying them back (5, 10).…”
Section: Resultsmentioning
confidence: 99%
“…Certainly there have been several attempts to research, quantify and expose the extent of harassment against disabled people in recent years (cf. Berzins et al, 2003;Wood and Edwards, 2005) and the British Crime Survey 2009/10 concluded that people with a disability are at a significantly greater risk of being a victim of violence compared to able bodied people. The EHRC (2009) also found that disabled people are at higher risk and experience greater levels of targeted violence in comparison to non-disabled people and that within the disabled population, people with learning disabilities and/or mental health conditions experience higher levels of targeted violence.…”
Section: Definitionmentioning
confidence: 99%
“…Across three studies, examining the experiences of people with mental health conditions between 47 per cent and 60 per cent of respondents reported that they had been harassed or abused in public because of their health problems (Read and Baker, 1996: 778 respondents;Wood and Edwards, 2005: 40 respondents;Kelly and McKenna, 1997: 100 respondents). In studies where comparators with non-disabled persons were used it becomes clear that harassment occurs more frequently for those with mental health conditions than for those without (Berzins et al, 2003, Wood andEdwards, 2005). For example, Berzins found that 60 per cent of those with mental health problems had experienced some form of harassment as compared to 44 per cent of the general population (Berzins et al, 2003).…”
Section: Evidence Of Harassment and Victimisation Of Disabled People mentioning
confidence: 99%